Genomic instability in pancreatic adenocarcinoma: a new step towards precision medicine and novel therapeutic approaches. (2nd August 2016) - Sahin, Ibrahim H.; Lowery, Maeve A.; Stadler, Zsofia K.; Salo-Mullen, Erin; Iacobuzio-Donahue, Christine A.; Kelsen, David P.; O'Reilly, Eileen M.
ABSTRACT: Pancreatic cancer is one of the most challenging cancers. Whole genome sequencing studies have been conducted to elucidate the underlying fundamentals underscoring disease behavior. Studies have identified a subgroup of pancreatic cancer patients with distinct molecular and clinical features. Genetic fingerprinting of these tumors is consistent with an unstable genome and defective DNA repair pathways, which creates unique susceptibility to agents inducing DNA damage. BRCA1/2 mutations, both germline and somatic, which lead to impaired DNA repair, are found to be important biomarkers of genomic instability as well as of response to DNA damaging agents. Recent studies have elucidated that PARP inhibitors and platinum agents may be effective to induce tumor regression in solid tumors bearing an unstable genome including pancreatic cancer. In this review we discuss the characteristics of genomic instability in pancreatic cancer along with its clinical implications and the utility of DNA targeting agents particularly PARP inhibitors as a novel treatment approach.